PENGELOLAAN LINGKUNGAN OUTDOOR DALAM MENCIPTAKAN SEKOLAH RAMAH ANAK - wahidah, Anita Solihatul; Us Alifah, Maya Rida; Hamidah, Akrimah; Wahyuni, Budi (Institut Agama Islam Ngawi, 2024)
Child-friendly schools must consider a school situation that is safe, clean and healthy, caring and cultured, a living environment, capable of guaranteeing, fulfilling, respecting children's rights and protection from violence, discrimination, other unfair treatment and guaranteeing children's participation in planning, policies, learning, supervision, and complaint mechanisms related to fulfilling children's rights and protection as well as instilling character values in students which include knowledge, awareness, or will, and actions to implement the values of goodness and benevolence, towards God Almighty, oneself, fellow human beings, the environment and nationality in order to become human beings with morals. This is in line with learning at the Dharma Wanita 2 Ngompro Kindergarten which applies an outdoor environment as a means of learning in order to create a child-friendly school according to needs. The research method used in this research is Qualitative Research Methodology which describes the results of observations, interviews and documentation with teacher participants, school principals and students. The research location is Dharma Wanita 2 Ngompro Kindergarten. Programs implemented at Dharma Wanita 2 Ngompro Kindergarten: inclusive curriculum, parent participation and involvement, anti-harassment and bullying, strengthening social skills, safe and friendly physical environment. This program is able to provide children with comfort and safety in learning at school so that it can be called a Child-Friendly School.